Management of Paediatric Psoriasis by Paediatricians: A Questionnaire-Based Survey - Andreas Pinter; Nicole Mielke; Bartosz Malisiewicz; Roland Kaufmann; Anke König (Dermatology and Therapy, 2020)
Abstract Introduction Paediatric plaque psoriasis (PedPso) in children and adolescents is often diagnosed and treated for the first time by paediatricians. An early onset of psoriasis is associated with a genetic family burden, higher severity of disease and increased risk of comorbidities, sometimes starting in childhood. However, little information is available on prevalence data and the clinical management of PedPso by paediatricians. Methods A total of 191 questionnaires were sent out to paediatricians regarding their management of PedPso, with a focus on prevalence, diagnosis, initiation of therapies, screening for comorbidities and collaboration with dermatologists. Of these, 95 (49.7%) were returned and evaluated anonymously. Results Only about one-half of the responding paediatricians reported being certain in their diagnosis of PedPso, even though they regularly see moderate-to-severely affected patients. The questionnaire revealed that there are clear differences in the general management of PedPso if the paediatrician is not certain of the diagnosis of psoriasis. Compared to paediatricians certain of their diagnosis, those who are uncertain less frequently perform whole-body inspection, screen for relevant comorbidities, such as psoriasis arthritis, metabolic syndrome or mental disorders, and prescribe the use of topical or systemic therapies. No responding paediatrician reported the use of modern systemic therapies, such as biologicals, even in severely affected children. The majority of respondents rated their cooperation with dermatologists as good. Conclusion The certainty of the diagnosis, the use of system therapies and the screening for comorbidity could improve the care of PedPso through targeted training of paediatricians and intensified interdisciplinary cooperation with dermatologist.